Torrent Control in the Doon Valley - Dalal, S. S.; Ullah, Wasi (Indian Forester, 1967)
The paper describes the torrent problems, the damage done and the bank protection measures found successful at the Dehra Dun Centre. A classification of torrent types has been attempted and important charaateristics of each type are mentioned. The physical processe involved in channel degradation and bank cutting are briefly brought out. Excess sediment is the major problem and is reaponsible for frequent channel shifting and inducing meanders in Saharanpur and Dehra Dun Districts. The performance of various bank and bad control measurea as applied to a torrent in Doon Valley has been discussed, Gabioni repelling spurs have given good results Other types of spurs like tree spur, log spur, etc., have been effective for limited period. Brush wood and boulder revetment have been successful for providing blanket protection. Bed control measures and their importance han been emphasized. The species suitable to stabilize sediment deposition have been given Pennisetum purpureum is one of the best species for this purpose. Deep planting has been suagested for good result. Maintenanve of works has been emphasized and timely maintenance can have lot of money spent on attending subsequent severe damage to the structures and other works.